Understanding the formation mechanism of mobile social networking site addiction: evidence from WeChat users - Gong, Mingchuan; Yu, Lingling; Luqman, Adeel (Behaviour & information technology, 2020)
The problematic use of mobile social networking sites (SNS) has become increasingly severe among a large proportion of users. However, only a few studies have investigated this issue. To understand the underlying mechanism of mobile SNS addiction, the current study examines the formation process of addiction with a particular focus on WeChat. This study uses the cognitive-behavioural model for its strong explanatory power in problematic information technology use. A field survey, which involved 335 WeChat users as subjects, was conducted to examine our study model. Results demonstrate that addictive behaviour is determined by individuals' perceived benefits (i.e. social and hedonic benefits) of mobile SNS. In turn, these benefits are influenced by sense of belonging and habit. We enhance the cognitive-behavioural model in the current context by identifying sense of belonging and habit as distal causes and perceived benefits as proximal causes. The practical implications of preventing mobile SNS addiction are also discussed in this research.